Was bedeutet Religion für Rechtsextremismus? Empirische Befunde zu Verbindungen zwischen Religiosität, Vorurteilen und rechtsextremen Einstellungen - Schneider, Verena (Zeitschrift für Religion, Gesellschaft und Politik, 2021)
German and European right-wing populists and extremists increasingly blame "Islam" or "the Muslims" for the emergence of societal conflicts. This development started, at the latest, with 9/11 and was reinforced by the refugee movements towards Europe in 2015. Muslims, along with Jews, are seen as the enemy. In Islamophobia as well as in antisemitism, religious adherence functions as a marker of rejection around which right-wing extremists and populists mobilize. On the other hand, religiosity on behalf of the social majority might also impact the formation of right-wing extremist attitudes. Prejudice against women and people with non-binary gender identities might play a role in this aspect. How exactly are religion, prejudice, and right-wing extremism related? By means of survey data, the authors first show correlations between right-wing extremism, Islamophobia, and antisemitism. Additionally, they explain the ambivalent role of religiosity: While dogmatic, fundamentalist religious beliefs as well as esotericism promote extremist attitudes, a social religiosity—that is, combining religious with social commitment—counteracts them. In conclusion, the authors explain the bridging function of prejudice against Muslims and Jews as well as against foreigners, refugees, Sinti and Romanies, women, and people with non-binary gender identities: Depreciating attitudes towards all of these groups can serve as a gateway to a right-wing worldview.